Ex situ plant conservation: Supporting species survival in the wild - Guerrant, Edward O (Island, 2012)
Faced with an alarming rate of loss of biodiversity, one strategy supported by many scientists is the use of zoos. This volume aims to win converts to ex situ efforts to protect plant genetic diversity